Application of Hydroxyethyl Methacrylate and Ethylene Glycol Methacrylate Phosphate Copolymer as Hydrogel Electrolyte in Enzymatic Fuel Cell. Issue 10 (6th October 2016) - Kizling, Michał; Biedul, Piotr; Zabost, Dariusz; Stolarczyk, Krzysztof; Bilewicz, Renata
Abstract: A composite polymer electrolyte is developed to improve the properties of electrochemical devices, such as lithium‐ion batteries, supercapacitors and fuel cells. Here we report the application of poly(2‐hydroxyethyl methacrylate) and ethylene glycol methacrylate phosphate copolymer as a pseudo solid state electrolyte for an enzymatic fuel cell. The phosphate groups present in the polymer chains ensure the stability of pH during fuel cell work and enable retaining water molecules in the polymer matrix through hydrogen bond formation. After optimization of synthesis conditions the maximum ionic conductivity of the hydrogel reached 0.028 S cm −1 and maximum loading of entrapped water was 50 % of hydrogel total mass. The hydrogel was employed as the electrolyte in electrochemical measurements of the enzymatic electrodes. The current density of fructose oxidation on the anode covered with single walled carbon nanotubes derivatized with amine groups and fructose dehydrogenase reached 5.2 mA cm −2 in 100 mM fructose concentration in the hydrogel and the current onset potential was −0.12 V vs Ag/AgCl. The cathode covered with multiwalled carbon nanotubes modified with naphthalene groups and laccase gave current density 0.56 mA cm −2 with onset potential of 0.6 V vs Ag/AgCl. Fully enzymatic fuel cell with hydrogel electrolyte exhibited maximum power density 0.2 mW cm −2 and higher stability in time than the cell with the same electrodes stored in water solution. Abstract :